1996
DOI: 10.1007/bf02282340
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel bacterial overgrowth in patients with alcoholic cirrhosis

Abstract: A total of 89 patients with alcoholic cirrhosis and 40 healthy subjects were included in a study to assess the prevalence of intestinal bacterial overgrowth and to analyze its relationship with the severity of liver dysfunction, presence of ascites, and development of spontaneous bacterial peritonitis (SBP). Bacterial overgrowth was measured by means of a breath test after ingestion of glucose. Intestinal bacterial overgrowth was documented in 27 (30.3%) of the 89 patients with alcoholic cirrhosis and in none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(36 citation statements)
references
References 25 publications
2
32
0
2
Order By: Relevance
“…The number of both anaerobic and aerobic bacteria was significantly higher in jejunal aspirates from patients with chronic alcohol abuse as compared with control subjects 6. Similar results were obtained in patients with alcoholic cirrhosis 7. Moreover, the degree of overgrowth correlates with the severity of cirrhosis 8.…”
Section: Alcohol-induced Changes In the Gut Microflorasupporting
confidence: 83%
“…The number of both anaerobic and aerobic bacteria was significantly higher in jejunal aspirates from patients with chronic alcohol abuse as compared with control subjects 6. Similar results were obtained in patients with alcoholic cirrhosis 7. Moreover, the degree of overgrowth correlates with the severity of cirrhosis 8.…”
Section: Alcohol-induced Changes In the Gut Microflorasupporting
confidence: 83%
“…Furthermore, administration of conjugated oral bile acids to ascitic cirrhotic animals increased bile acid secretion, eliminated intestinal bacterial overgrowth, decreased bacterial translocation and endotoxaemia and increased survival [38]. Translating these findings to the clinical setting, Casafont Morencos et al [39] demonstrated that 30 % of alcoholic cirrhotic patients had intestinal bacterial overgrowth on the basis of breath testing compared with none in the healthy controls and, moreover, the prevalence of spontaneous bacterial peritonitis was significantly higher in patients who had intestinal bacterial overgrowth than in patients who did not. It has also been demonstrated [40] that the incidence of bacterial overgrowth of the small intestine was much higher in cirrhotic patients with bacterial peritonitis than in those without spontaneous bacterial peritonitis.…”
Section: Intestinal Bacterial Overgrowth and Bacterial Translocation mentioning
confidence: 94%
“…Bacterial overgrowth of the small intestine may occur in certain disease states, and is defined as at least 10 5 total CFU/mL in jejunal secretions. Small intestinal bacterial overgrowth is prominent in both cirrhotic rats with ascites and patients with cirrhosis [24-27], and is thought to be the most common site of bacterial translocation [28]. It is related to the severity of liver disease [27], and increases the risk of bacterial translocation and infection [24, 29, 30].…”
Section: 0 Novel Strategiesmentioning
confidence: 99%
“…Small intestinal bacterial overgrowth is prominent in both cirrhotic rats with ascites and patients with cirrhosis [24-27], and is thought to be the most common site of bacterial translocation [28]. It is related to the severity of liver disease [27], and increases the risk of bacterial translocation and infection [24, 29, 30]. Proposed strategies to target this bacterial overgrowth involve decreasing the overall bacterial burden or changing the taxonomy of intestinal microbes to favor the growth of anaerobic bacteria [Figure 3].…”
Section: 0 Novel Strategiesmentioning
confidence: 99%